ANALISIS MORFOLOGI DAN PERUBAHAN GARIS PANTAI TAHUN 2009- 2021 DI WILAYAH PANTAI BANTOL KABUPATEN MALANG - Zulvan Yusuf Fadilah; nur afifah; Siti Sarah Rodhiah Mariza; Titah Indit Pakarti; Ferryati Masitoh (Universitas Negeri Padang, 2022)
Coastlines can change rapidly as a result of natural physical processes and human activities. This research is a quantitative study with a numerical approach with the aim of knowing the condition of shoreline changes from time to time. The research study area is Bantol Beach which is located in Kedungsalam Village, Donomulyo District, Malang Regency, East Java. The data is obtained through direct measurements in the field using a total station for 2021, and satellite images for the years 2009-2019. Landform units of Bantol Beach are beach ridge and spit. In field measurements, the length of the coastline is 296.34 m, but it has a fluctuating nature when compared to the previous year. The wave height varies with the highest value reaching 1.1 m and the lowest being 0.1 m. The bottom slope of the coast is divided into two, namely 4% in the west and 3% in the east. Abrasion and accretion rates at Bantol Beach have a higher ratio of abrasion rates than accretion, respectively, with abrasion values of 2411 m² and 1110 m², while accretion values are 1459.7 m² and 254.97 m², respectively. The low tide and high tide zones continue to experience accretion but are volatile and dominated by abrasion.